Correlation between Supportive Care Needs of Women with Breast Cancer and Quality of Life of their Family Caregivers - Mozhgan Mohammadzadeh Nimekari; Marzieh Saei Ghare Naz; Yaghoub Ashouri Taziani; Maliheh Nasiri; Mohammad Reza Evazi; Amin Shafizad; Giti Ozgoli (Shiraz University of Medical Sciences, 2019)
Background: Breast Cancer is highly prevalent among women. The supportive care needs of such patients not only affect their quality of life (QoL) but also that of their family caregivers. The present study aimed to assess the correlation between the supportive care needs of women with breast cancer and the QoL of their family caregivers. Methods: The present cross-sectional study was conducted from September 2017 to June 2018. The target populations were breast cancer patients (N=150) and their primary family caregivers (N=150) who attended the Omid Chemotherapy and Radiotherapy Center affiliated with Hormozgan University of Medical Sciences, Bandar Abbas, Iran. Data collection tools included a demographic information form, the Supportive Care Needs Survey-Short Form 34, and the Caregiver Quality of Life Index-Cancer Scale. The data were analyzed using SPSS software (version 22.0) with descriptive statistics and Pearson's correlation coefficient. PResults: The mean age of the patients was 45.76±10.44 years. Of the family caregivers, 99 (66%) were the patients 'spouses. Of the different dimensions of the supportive care needs, the score for the physical needs (40.60±23.50) was the highest. In terms of the QoL of the family caregivers, mental and emotional burden scored the highest (20.19±7.38). There was a significant correlation between the caregivers' mental and emotional burden and the physical needs of the patients (r=0.19, P=0.02). Conclusion: The result of the present study showed that physical needs were the most common supportive care needs of patients with breast cancer. Such needs also significantly undermined the QoL of the caregivers in terms of emotional burden and financial concerns.